Projected health and economic effects of nonavalent versus bivalent human papillomavirus vaccination in preadolescence in the Netherlands - Birgit Sollie; Johannes Berkhof; Johannes A. Bogaards (BMC Medicine)
Abstract Background Most European countries offer human papillomavirus (HPV) vaccination through organised immunisation programmes, but the choice of vaccine varies. We compared the expected health and economic effects of the currently used bivalent vaccine, targeting HPV-16/18, and the nonavalent vaccine, targeting seven additional genotypes, for the Netherlands. Methods We estimated the incremental impact of nonavalent versus bivalent vaccination in a cohort of 100,000 girls and 100,000 boys offered vaccination at age 10, by projecting type-specific infection risk reductions onto expected number of cervical screening outcomes, HPV-related cancers, and treatments for anogenital warts and recurrent respiratory papillomatosis (RRP). In the base-case, we assumed two-dose vaccination with 60% uptake, lifelong partial cross-protection against HPV-31/33/45 for the bivalent vaccine and EUR 25 extra cost per dose for the nonavalent vaccine. Cost-effectiveness was assessed from a healthcare provider perspective by comparing the incremental cost-effectiveness ratio (ICER) per life-year gained (LYG) with the Dutch threshold of EUR 20,000/LYG. Results Compared with bivalent vaccination, nonavalent vaccination prevents an additional 1320 high-grade cervical lesions, 70 cancers, 34,000 anogenital warts episodes and 30 RRPs and generates EUR 4.1 million discounted savings from fewer treatments. The ICER is EUR 5489 (95% credible interval: 3765; 7019)/LYG in the base-case and exceeds the cost-effectiveness threshold only if the cross-protection for the bivalent vaccine extends permanently to non-31/33/45 genotypes or if the vaccine efficacy wanes past age 20 for both vaccines. Conclusions Sex-neutral vaccination with the nonavalent vaccine is likely to be cost-effective. Long-term monitoring of type-specific vaccine effectiveness is essential because of the impact of cross-protection and waning efficacy on cost-effectiveness.